How can we use social network analysis to better understand Chimpanzee and Gorilla sociality and communication? - Anna Ilona Roberts; Sam George Bradley Roberts (Animal Cognition)
Abstract An important element in understanding the evolution of human sociality is to understand the factors that governed the evolution of social organisation in our closest living relatives. The ‘social brain hypothesis’ proposes that the complex social world of primates is especially cognitively demanding, and that this imposed intense selection pressure for increasingly large brains. Group size in primates is strongly correlated with brain size but exactly what makes larger groups more ‘socially complex’ than smaller groups is still poorly understood. Chimpanzees and Gorillas are among our closest living relatives and they exhibit remarkable diversity in various aspects of their social organisation both within and across species. They are thus excellent species in which to investigate patterns of sociality and social complexity in primates, and to inform models of human social evolution. We propose a program of research that will provide the first systematic insight into how social structure differs in small, medium and large groups of Chimpanzees and Gorillas, to explore what makes larger groups more socially complex than smaller groups. Further, we propose to investigate how these variations in social structure in different size groups are affected by the social organisation of the species. Chimpanzees live in a fluid fission-fusion social system, whereas Gorillas have more stable, cohesive groups. To carry out both the within and between species comparisons, we advocate use of social network analysis, which provides a novel way to describe and compare social structure. This program of research will therefore lead to a new, systematic way of comparing social complexity across species, something that is lacking in current comparative studies of social structure. Considering that hominins were likely characterized by a fission-fusion social structure, comparing the social complexity of such systems with that of more stable groups may yield valuable insights into the evolution of human sociality.